2022
DOI: 10.12688/f1000research.125998.1
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems of asymptomatic or mildly symptomatic COVID-19 patients in hospitel in Thailand: A cross-sectional study

Abstract: Background There is evidence that patients with COVID-19 have a higher prevalence of mental health problems than the normal population. This study aimed to investigate the prevalence of mental health problems and their associated factors in patients with asymptomatic or mildly symptomatic in the hospitel in Thailand. Methods Mental health problems were evaluated using the Depression, Anxiety, and Stress Scale - 21 items, and Patient Health Questionnaire-9. The prevalence of mental health problems was presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Recent studies ( Liu et al, 2021 ; Lerthattasilp et al, 2020 ; AlRasheed et al, 2022 ) found that the prevalence of anxiety symptoms, depression, stress and insomnia were relatively high (26.9 %, 32.3 %,25.8 %, and 52.7 %, respectively) in COVID-19 patients admitted to hospitels in Thailand, especially on the first day of admission ( Kerdcharoen et al, 2022 ). These mental health issues could affect the quality of life and recovery process ( Triantafillou et al, 2022 ; Azizi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies ( Liu et al, 2021 ; Lerthattasilp et al, 2020 ; AlRasheed et al, 2022 ) found that the prevalence of anxiety symptoms, depression, stress and insomnia were relatively high (26.9 %, 32.3 %,25.8 %, and 52.7 %, respectively) in COVID-19 patients admitted to hospitels in Thailand, especially on the first day of admission ( Kerdcharoen et al, 2022 ). These mental health issues could affect the quality of life and recovery process ( Triantafillou et al, 2022 ; Azizi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%